Volumetric modulated arc therapy total body irradiation in pediatric and adolescent/young adult patients undergoing stem cell transplantation: Early outcomes and toxicities. Issue 6 (4th April 2022) - Marquez, Cesar; Hui, Caressa; Simiele, Eric; Blomain, Erik; Oh, Justin; Bertaina, Alice; Klein, Orly; Shyr, David; Jiang, Alice; Hoppe, Richard T.; Kovalchuk, Nataliya; Hiniker, Susan M.
Abstract: Introduction: Total body irradiation (TBI) is an important component of many conditioning regimens for hematopoietic stem cell transplantation (HSCT), most commonly used in pediatric and adolescent/young adult (AYA) patients. We aimed to evaluate outcomes and toxicities among pediatric and AYA patients treated with TBI utilizing volumetric modulated arc therapy total body irradiation (VMAT‐TBI). Methods: We reviewed pediatric and AYA patients treated with VMAT‐TBI at our institution from 2019 to 2021. Data on patient and disease characteristics, treatment details, outcomes and toxicities were collected. Overall survival (OS) and relapse‐free survival (RFS) were analyzed using the Kaplan–Meier method. Results: Among 38 patients, 16 (42.1%) were treated with myeloablative regimens and 22 (57.9%) with nonmyeloablative regimens. Median age was 7.2 years (range: 1–27) and median follow‐up was 8.7 months (range: 1–21). Lungs D mean was 7.3 ± 0.3 Gy for myeloablative regimens (range: 6.8–7.8). Kidneys were spared to average mean dose of 71.4 ± 4.8% of prescription dose. Gonadal sparing was achieved for patients treated for nonmalignant diseases to D mean of 0.7 ± 0.1 Gy. No patient experienced primary graft failure; one (2.6%) experienced secondary graft failure. The most common grade 1–2 acute toxicities were nausea (68.4%) and fatigue (55.3%). Mucositis was the most common grade 3–4 acute toxicity, affecting 39.5% of patients. There were no cases of pneumonitis or nephrotoxicity attributable to TBI. Conclusion: VMAT‐TBI offers increased ability to spare organs at risk in pediatric and AYA patients undergoing HSCT, with a favorable acute/subacute toxicity profile and excellent disease control.